The influence of formulation ratio and emulsifying settings on tri-fuel (diesel–ethanol–biodiesel) emulsion properties - M. Mukhtar, N. A.; Abd Rashid, Abd Aziz; Hagos, F. Y.; M. M., Noor; K., Kadirgama; R., Mamat; Abdul Adam, Abdullah (MDPI AG, 2019)
In this study, an alternative fuel for compression ignition (CI) engines called tri-fuel emulsion was prepared using an ultrasonic emulsifier. The objective of the study is to investigate the effect of emulsifying settings and formulation ratio on the physicochemical properties of tri-fuel emulsions. Design of experiment (DOE) with the two-level factorial design was employed to analyze the effect of emulsifying settings such as time, amplitude, and cycle along with the variation ratio of tri-fuel emulsion components as control factors. Numbers of responses identified were important parameters that may contribute to microexplosion phenomenon in CI engine. Analysis of variance (ANOVA) was carried out for each response, and the results indicated that density, dynamic viscosity, surface tension, and average droplet size were influenced by specific preparation control factors. Furthermore, interaction among the control factors was found to affect the responses as well. Interaction means the effect of two factors together is different than what would be expected from each factor separately. Besides, the stability of the tri-fuel emulsion was observed for three months. Furthermore, a qualitative approach with a multiobjective lens digital microscope revealed the geometry of freshly made dispersed tri-fuel emulsion droplets. Microscopic examination on tri-fuel emulsion droplets has shown that the dispersed ethanol capsulated within diesel with the help of biodiesel is similar to a water in diesel emulsion and is dissimilar to commercial diesel mixed with fatty acid methyl esters found in the market.